A autenticidade na filosofia de Vilém Flusser - Guilherme de Araujo Freitas (2017)
Throughout Vilem Flussers work it is possible to find the authenticity concept several times. However, we cannot say that it is always used by the philosopher in the same way. Our purpose is to define the concept of authenticity taking into account how it is used, in different contexts, searching to understand its relations with other concepts of Flussers philosophy. In our hypothesis, three definitions of the concept may be worked out. The first is based on the identity between authenticity and truth; the second, on the identity between authenticity and legitimacy; and the third, on the possible relation between the truth and legitimacy. First I am going to present the philosopher`s linguistic conception of reality; then I am going to think about the correspondence to reality that characterizes the classic definition of truth. After that, I am going to try to justify the legitimacy in relation to the concept of authenticity with Flussers reflection about rationality models, which is determinant not only about his conception of the world, but also about human action over it in order to modify it. Finally, I am going to try to establish relations among the meanings of authenticity that set up the definitions previously mentioned, in an approach that considers Flussers philosophy elements as a whole.